Hierarchical and Hybrid Organizational Structures in Open-source Software Projects: A Longitudinal Study - Joblin, Mitchell; Eckl, Barbara; Bock, Thomas; Schmid, Angelika; Siegmund, Janet; Apel, Sven (ACM transactions on software engineering and methodology, 2023)
Despite the absence of a formal process and a central command-and-control structure, developer organization in open-source software (OSS) projects are far from being a purely random process. Prior work indicates that, over time, highly successful OSS projects develop a hybrid organizational structure that comprises a hierarchical part and a non-hierarchical part. This suggests that hierarchical organization is not necessarily a global organizing principle and that a fundamentally different principle is at play below the lowest positions in the hierarchy. Given the vast proportion of developers are in the non-hierarchical part, we seek to understand the interplay between these two fundamentally differently organized groups, how this hybrid structure evolves, and the trajectory individual developers take through these structures over the course of their participation. We conducted a longitudinal study of the full histories of 20 popular OSS projects, modeling their organizational structures as networks of developers connected by communication ties and characterizing developers’ positions in terms of hierarchical (sub)structures in these networks. We observed a number of notable trends and patterns in the subject projects: (1) hierarchy is a pervasive structural feature of developer networks of OSS projects; (2) OSS projects tend to form hybrid organizational structures, consisting of a hierarchical and a non-hierarchical part; and (3) the positional trajectory of a developer starts loosely connected in the non-hierarchical part and then tightly integrate into the hierarchical part, which is associated with the acquisition of experience (tenure), in addition to coordination and coding activities. Our study (a) provides a methodological basis for further investigations of hierarchy formation, (b) suggests a number of hypotheses on prevalent organizational patterns and trends in OSS projects to be addressed in further work, and (c) may ultimately guide the governance of organizational structures.